2020
DOI: 10.21606/drs.2020.182
|View full text |Cite
|
Sign up to set email alerts
|

Design and Science: A workshop-based approach for identifying commercial opportunities in universities

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…From diving into these complex contexts, students can measure possibilities and practical constraints of everyday life. Where, following a Double Diamond method providing divergent and creative assessments, new inputs can arise not only from a product but from a broad array of possibilities (Mesa et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…From diving into these complex contexts, students can measure possibilities and practical constraints of everyday life. Where, following a Double Diamond method providing divergent and creative assessments, new inputs can arise not only from a product but from a broad array of possibilities (Mesa et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we believe there is an opportunity for designers to help manufacturers adopt new technologies, as their ability to explore and communicate ideas through different means can help translate complex information in multidisciplinary teams [59]. Furthermore, regardless of the field, designers have shown to be good at exploring opportunities to innovate using emerging technologies [60] and demonstrating their potential [61]. Moreover, the designers' knowledge of manufacturing processes and materials allowed them to fully understand Eudaemon's needs even without visiting their facilities.…”
Section: Designers' Opportunities In Advanced Manufacturingmentioning
confidence: 99%
“…Exploring many opportunities to exploit emerging technologies is crucial for introducing technologies to market; more options enrich the selection process and facilitate innovation, allowing a more careful use of the vast resources needed to develop a new product (Brem and Voigt, 2009). As successful technology companies explore opportunities broadly, and designers have shown to be good at it, it is evident that designers' contributions can help address some of the challenges of developing university technology (Mesa et al, 2019, Mesa et al, 2020. Second, designers also help demonstrate technology performance outside laboratory settings in the context of products through prototyping.…”
Section: Design's Contribution To Scientific Research Commercialisationmentioning
confidence: 99%
“…First, existing works have reported that designers help identify plausible applications to connect technologies to suitable markets. This can be achieved through; stimulating creativity via problem reframing and visualisation (Rust, 2004), market research (Design Council, 2015, Driver et al, 2011, facilitating creativity workshops (Design Council, 2015, Mesa et al, 2020 and prototyping (Page andJohn, 2020, Thong andKuys, 2012). Exploring many opportunities to exploit emerging technologies is crucial for introducing technologies to market; more options enrich the selection process and facilitate innovation, allowing a more careful use of the vast resources needed to develop a new product (Brem and Voigt, 2009).…”
Section: Design's Contribution To Scientific Research Commercialisationmentioning
confidence: 99%